2022
DOI: 10.1186/s13046-022-02254-z
|View full text |Cite
|
Sign up to set email alerts
|

FTO suppresses glycolysis and growth of papillary thyroid cancer via decreasing stability of APOE mRNA in an N6-methyladenosine-dependent manner

Abstract: Background N6-methyladenosine (m6A) modification is the most common chemical modification in mammalian mRNAs, and it plays important roles by regulating several cellular processes. Previous studies report that m6A is implicated in modulating tumorigenesis and progression. However, dysregulation of m6A modification and effect of m6A demethylase fat-mass and obesity-associated protein (FTO) on glucose metabolism has not been fully elucidated in papillary thyroid cancer (PTC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 58 publications
1
75
0
1
Order By: Relevance
“…However, m 6 A methylation modifiers act as a double-edged sword in the regulation of cellular processes associated with glycolysis, which may depend on the large number of RNA-binding proteins (RBPs), including both m 6 A methylation reading and non-reading proteins, and their recognition sites. Huang et al [ 66 ] suggested that FTO suppresses APOE through IGF2BP2-mediated m 6 A methylation and inhibits glycolytic metabolism in PTC through regulating the IL-6/JAK2/STAT3 signaling pathway, thereby retarding thyroid cancer cell growth. Correspondingly, YTHDC1-mediated enhancement of miR-30d suppressed pancreatic tumorigenesis via attenuation of RUNX1-induced transcriptional activation of the Warburg effect [ 67 ].…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…However, m 6 A methylation modifiers act as a double-edged sword in the regulation of cellular processes associated with glycolysis, which may depend on the large number of RNA-binding proteins (RBPs), including both m 6 A methylation reading and non-reading proteins, and their recognition sites. Huang et al [ 66 ] suggested that FTO suppresses APOE through IGF2BP2-mediated m 6 A methylation and inhibits glycolytic metabolism in PTC through regulating the IL-6/JAK2/STAT3 signaling pathway, thereby retarding thyroid cancer cell growth. Correspondingly, YTHDC1-mediated enhancement of miR-30d suppressed pancreatic tumorigenesis via attenuation of RUNX1-induced transcriptional activation of the Warburg effect [ 67 ].…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…In similar with c-MYC, oncogene SOX2 is highly susceptible to m 6 A modification 165 , 166 . In thyroid cancer, m 6 A demethylase FTO inhibits cell growth and glycolysis by reducing the mRNA stability of target, APOE in IGF2BP2-mediated m 6 A-dependent manner 167 . IGF2BP2 also promotes lymphatic metastasis and epithelial-mesenchymal transition (EMT) of head and neck squamous carcinoma cells by stabilizing slug mRNA in an m 6 A-dependent manner 168 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…FTO suppresses the oncogenesis of pancreatic cancer by inhibiting Wnt signaling as well as demethylating PJA2 [68]. In papillary thyroid cancer (PTC), Huang et al, found that FTO restrains the stability of Apolipoprotein E (APOE), repressing the glycolysis and growth of PTC in an m 6 A-IGF2BP2-mediated manner [69]. Another type of demethylase, ALKBH5, was found to promote oncogenesis of AML selectively in an m 6 A-dependent manner [70].…”
Section: Erasers In Oncogenesismentioning
confidence: 99%
“…METTL3 was found to upregulate glycolysis in CRC by stabilizing HK2 and SLC2A1 in an m 6 A-IGF2BP2/3-dependent manner, leading to cancer progression [41]. Conversely, FTO represses the glycolysis of PTC by destabilizing APOE, thus restraining the growth of cancer [69]. By modulating hypoxia and glycolysis in the TME, altering m 6 A modifications may serve as a therapeutic strategy in treating cancers, though more in-depth research is required.…”
Section: Conditioning Tumor Microenvironment and Immunotherapymentioning
confidence: 99%